Treatment of secondary brain injury by perturbing postsynaptic density protein-95-NMDA receptor interaction after intracerebral hemorrhage in rats. Issue 8 (August 2019) - Wang, Zhifeng; Chen, Zhouqing; Yang, Junjie; Yang, Ziying; Yin, Jia; Duan, Xiaochun; Shen, Haitao; Li, Haiying; Wang, Zhong; Chen, Gang
Postsynaptic density protein-95 (PSD95) plays important roles in the formation, differentiation, remodeling, and maturation of neuronal synapses. This study is to estimate the potential role of PSD95 in cognitive dysfunction and synaptic injury following intracerebral hemorrhage (ICH). The interaction between PSD95 and NMDA receptor subunit NR2B-neurotransmitter nitric oxide synthase (nNOS) could form a signal protein complex mediating excitatory signaling. Besides NR2B-nNOS, PSD95 also can bind to neurexin-1–neuroligin-1 to form a complex and participates in maintaining synaptic function. In this study, we found that there were an increase in the formation of PSD95-NR2B-nNOS complex and a decrease in the formation of neurexin-1–neuroligin-1-PSD95 complex after ICH, and this was accompanied by increased neuronal death and degeneration, and behavior dysfunction. PSD95 inhibitor Tat-NR2B9c effectively inhibited the interaction between PSD95 and NR2B-nNOS, and promoted the formation of neurexin-1–nueuroligin-1-PSD95 complex. In addition, Tat-NR2B9c treatment significantly reduced neuronal death and degeneration and matrix metalloproteinase 9 activity, alleviated inflammatory response and neurobehavioral disorders, and improved the cognitive and learning ability of ICH rats. Inhibition of the formation of PSD95-NR2B-nNOS complex can rescue secondary brain injury and behavioral cognitive impairment after ICH. PSD95 is expected to be a target for improving the prognosis of patients with ICH.